Portosystemic collaterals in living donor liver transplantation: What is all the fuss about?. Issue 4 (April 2017) - Reddy, Mettu Srinivas; Rela, Mohamed
Abstract : Portosystemic collaterals are a common finding in patients with cirrhosis undergoing liver transplantation. Recently, there has been a renewed interest regarding their significance in the setting of living donor liver transplantation (LDLT) due to concerns of graft hypoperfusion or hyperperfusion and its impact on early posttransplant outcomes. Presence of these collaterals has greater significance in the LDLT setting when compared with the deceased donor liver transplantation setting as dictated by the difference in the physiology of partial liver grafts. We discuss current thinking of portal flow dynamics and the techniques for dealing with this clinical problem. Liver Transplantation 23 537–544 2017 AASLD.